Current concepts of the pathogenesis of non-alcoholic fatty liver disease - Evgenia Pavlovna Kosobyan; Olga Mikhailovna Smirnova (Сахарный диабет)
Non-alcoholic fatty liver disease (NAFLD) - common chronic liver disease, characterized by pathological accumulation of fat droplets, not associatedwith alcohol. NAFLD is often a component of other diseases such as metabolic syndrome, diabetes, obesity, and contributes to the prevalence of CVDamong the population.Asymptomatic disease, the difficulty of diagnosis, the lack of a unified concept of treatment NAFLD - topical issues that require more in-depth studyand worthy of attention a wide range of specialists.